Cyclic RGD Pentapeptide Cilengitide Enhances Efficacy of Gefitinib on TGF-β1-Induced Epithelial-to-Mesenchymal Transition and Invasion in Human Non-Small Cell Lung Cancer Cells - Jeong, Jisu; Kim, Jiyeon (Frontiers in Pharmacology, 2021)
During non-small cell lung cancer (NSCLC) progression, transforming growth factor (TGF)-β mediated epithelial-to-mesenchymal transition (EMT) is an important process leading to high mortality and poor prognosis. The EMT is a fundamental process for morphogenesis characterized by the transformation of cancer cells into invasive forms that can be transferred to other organs during human lung cancer progression. Gefitinib, an epidermal growth factor receptor (EGFR) inhibitor, has shown anti-proliferative effects in EGFR-mutated NSCLC cells and an inhibitory effect on migration and invasion of NSCLC cells to other organs. In this study, we evaluated the combinatorial treatment effect of cilengitide, a cyclic RGD pentapeptide, on TGF-β1-induced EMT phenotype and invasion. Gefitinib suppressed the expression of TGF-β1-induced mesenchymal markers by inhibiting Smad and non-Smad signaling pathways. Cilengitide enhanced the inhibitory effect of gefitinib on TGF-β1-induced expression of mesenchymal markers, phosphorylation of Smad2/3, and invasion of NSCLC A549 cells. We suggested that the use of cilengitide can improve the efficacy of anti-cancer drugs in combination drug-based chemotherapy. These results provide an improved therapeutic strategy for treating and preventing EMT-related disorders, such as NSCLC, lung fibrosis, cancer metastasis, and relapse.